Microbiome diversity across physicochemical gradient in low-medium enthalpy springs at the Sierra Madre Oriental eastern flank, northeastern Mexico - Juárez-Aragón, María Cruz; Pantoja-Irys, Jerjes R.; de la Rosa-Manzano, Edilia; Garrido-Olvera, Lorena; Mujica-Sánchez, Hugo; Trejo-De León, Carlos Rafael; Vázquez-Lobo, Alejandra (Frontiers in Microbiology, 2025)
IntroductionBacterial communities are fundamental to the functionality of thermal springs where they engage in essential processes such as the oxidation of sulfur, reduction of nitrates, carbon fixation, production of unique metabolites, and stabilization of microbial trophic networks. Northeastern Mexico presents a diverse array of thermal springs located within tropical karst systems situated among folded mountains and ancient inactive karstic regions. The geological complexity of these environments indicates a substantial potential for microbiome diversity; however, the composition and functional dynamics of microbial communities in these springs have not been thoroughly investigated.MethodsThis study involved the collection of water samples from six hot springs, to characterize the planktonic microbiome using advanced metagenomic sequencing techniques. Additionally, we examined the relationship between microbial composition and physicochemical parameters.ResultsOur analysis identified a total of 425 microbial species, which included 409 bacterial species, 13 eukaryotic organisms, and 3 archaeal taxa. The Ojo Caliente and Mainero Azufroso springs displayed the highest microbial diversity, whereas the Balneario El Bañito and Taninul springs exhibited the lowest. The Phyum Pseudomonadota was the predominant across the majority of springs, while Campylobacterota and Chlorobiota were specifically identified in the less diverse Balneario El Bañito and Taninul springs, respectively. A total of 30 indicator species were identified, predominantly in El Bañito and Potrero Prieto springs, emphasizing the distinctiveness of their microbial environments. Moreover, we found that electrical conductivity and bicarbonate concentration had a significant impact on the structure of this microbial communities.DiscussionThis study highlights the ecological importance of these unique ecosystems in northeastern Mexico, with the Mainero Azufroso and Ojo Caliente springs identified as reservoirs of high microbial diversity.